Watak Peradaban dalam Epistimologi Ibnu Khaldun - Hafidz Hasyim (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2010)
This article investigates Ibn Khaldun's thought on the nature of civilization from a historical perspective and his thought on the nature of civilization as an epistemological foundation. It was found that the nature of civilization is epistemological because the study of the nature of civilization is a new method in discovering the substance of history. Furthermore, the nature civilization is related to the nature of human beings for having produced sciences in its history. According to Ibn Khaldun, our system of thought is limited in two ways: the relation of physical systems to both perception and intellectual, and the relation of physical systems to spirituality. In this context, Ibn Khaldun classifies sciences into intellectual and revelational sciences.